The Politics of Religious Non-Interference: Islamic Legal Reform in Colonial India - Siddiqui, Sohaira Z. (Die Welt des Islams, 2025)
The 1929 Child Marriage Restraint Act (cmra), initially propounded as the Sarda Bill, became the first law related to marriage enacted in colonial India to be universally applicable to all subjects regardless of personal religious affiliations. Though formally adopted before Indian independence, the crma was advanced and passed by the newly formed Central Legislative Assembly which consisted primarily of Indians. As a result, the cmra garnered vociferous debates within both Muslim and Hindu communities and signaled a new challenge for religious communities which was distinct from British colonial legal logics. The focus of this article will be on one Muslim scholarly engagement with the cmra, that of Mufti Kifāyatallāh Dihlawī, the President of the Jamʿiyyat-i ʿUlamāʾ-i Hind (juh) and a highly influential Deobandi scholar. By navigating the contours of his legal debate surrounding the cmra, this article explores how the process of Islamic legal reform in the late colonial period in India was met with a new set of challenges as Indians gaining legislative authority sought to enact legal reforms that were seen as impinging on the rights of religious communities. And while, in this case, Muslim juristic opinions were sought, they could ultimately be trumped by larger social and political forces. More broadly, this article demonstrates that as India inched towards self-governance, competing groups and entities sought to claim communal representation of Muslims, and in the process, arguments made by religious scholars, even if they were recognized as being representative of broad Muslim sentiments, could be dismissed by emerging legal logics which supported the nationalizing tendencies of the Imperial Legislative Assembly over and above the rights of religious communities.